The Implementation Of Teaching Writing To The Eighth Grade Students Of SMP N 2 Sawit Boyolali Semester Two In 2013/2014 - Priyanto, Dedy; , Dr. Dwi Haryanti, M.Hum; , Drs. Djoko Srijono, M.Hum (2014)
This study aims at describing the implementation of teaching writing to the eighth grade students of SMP N 2 Sawit Boyolali semester two in 2013/2014 academic year and to describe problem faced by teacher and students in teaching writing process. This is descriptive qualitative research. The researcher collected the data by observing the English class and interviewing teacher and students. The data include field note of observation, interview script, and syllabus. While, the methods of collecting the data are observation, interview, and document. The technique used in analyzing data is as follows collecting the data of the observation and interviewing, analyzing the data from the result of observation and interview, and concluding the result and giving suggestion. The objectives of teaching writing at the eighth grade students of SMP N 2 Sawit Boyolali are (1) to help the students develop their writing skills. In the classroom activities, teacher gives the students a drill. (2) to enable the students in understanding English as a means of communication. (3) to enable the students in being active in practicing English in written form. The material for teaching writing taken from worksheet related with syllabus. Media that the teacher uses are worksheet and LCD projector. In process of teaching writing, the teacher gives the opportunities for the children to participate in activities in the class. So the objective of teaching English is achieved. The teacher used mixing techniques in teaching writing process such as, imitative or writing down, intensive or controlled writing, self-writing, and real writing. In the evaluation, the teacher used the daily test, mid test, and final test. Mid test and final test are the test made by the government to measure achievement at students nationally. The daily test is a test made by the teacher to measure the students ability especially in writing skill. In daily evaluation the teacher gives the daily assignment and homework. The problems faced by the teacher in teaching writing are the discipline of the students, the students do not do their homework, and the students don't bring dictionary when they join the class. While, the problem faced by the students in writing is several students do not want to write.